Comparing the Effectiveness of Paradoxical Therapy and Cognitive-Behavioral Therapy on Body image in Women with Body Dysmorphic Disorder - Mahboubi, Elham; Shaker Dioulagh, Ali; Khademi, Ali; Asayesh, Mohammad Hassan (Psychology of Woman Journal, 2026)
Objective: The aim of this study was to compare the effectiveness of paradoxical therapy and cognitive-behavioral therapy (CBT) on body image in women with body dysmorphic disorder (BDD).Methods and Materials: A quasi-experimental design with pretest, posttest, and three-month follow-up and a control group was used. The statistical population comprised all women seeking cosmetic surgery who attended aesthetic clinics in Tehran between October–December 2023. To identify individuals with BDD symptoms, the Body Dysmorphic Evaluation Scale (Rabaii et al., 2011) was administered to all clinic visitors. After scoring, those with elevated scores were evaluated through a diagnostic interview by a clinical psychologist. Ultimately, 45 participants were purposively selected and randomly assigned to two experimental groups and one control group. Research instruments included the Body image Questionnaire (Soweto and Garcia, 2002) and the BDD scale (Rabaii et al., 2020). Data were analyzed in SPSS-2 using repeated-measures ANOVA.Findings: Results indicated no significant difference between the Paradoxical therapy and CBT groups in body image scores (F = 0.886, p > .05). However, the statistical analyses confirmed that both interventions significantly reduced body image relative to the control condition among women with body dysmorphic disorder.Conclusion: Based on these findings, it can be concluded that the effectiveness of Paradoxical therapy and CBT in improving body image among women with body dysmorphic disorder does not differ significantly.